2018
DOI: 10.1590/0100-29452018586
|View full text |Cite
|
Sign up to set email alerts
|

Mango Propagation

Abstract: -ThisChapter has the objectives to search, through the review of the available literature, important informations on the evolution of mango propagation regarding theoretical and practical aspects from cellular base of sexual propagation, nursery structures and organizations, substrate compositions and uses, importance of rootstock and scion selections, also it will be described the preparation and transport of the grafts (stem and bud) as well as the main asexual propagation methods their uses and practices. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Traditionally, 'Ataulfo' mango orchards consist of monoculture plantations, derived from clones propagated by grafting on native cultivar patterns [14,15]. Here, we found that planting designs including a suitable pollen donor (e.g., 'Haden') increased the yield and economic input of these orchards.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Traditionally, 'Ataulfo' mango orchards consist of monoculture plantations, derived from clones propagated by grafting on native cultivar patterns [14,15]. Here, we found that planting designs including a suitable pollen donor (e.g., 'Haden') increased the yield and economic input of these orchards.…”
Section: Discussionmentioning
confidence: 92%
“…One of the leading proposed causes of nubbins in 'Ataulfo' is the presence of a late selfincompatibility mechanism [10], also found in other mango cultivars [1,[11][12][13]. Given that mango cultivars are propagated by grafting [14,15], self-incompatible pollen deposition may increase in orchards cultivated with only one cultivar [16]. One of the strategies used by some mango producers is planting trees of a compatible cultivar ("pollen donor", from now on) with the cultivar of commercial interest on the same orchard to minimize the harmful effects of inbreeding depression since it has been observed that this practice increases the production of fruits in other crops such as pears [17], apples [18,19], and also in other mango cultivars [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Mango seedlings are commercially propagated by grafting (Pinto et al, 2018). However, little is known about the selection and use of suitable rootstocks for producing quality grafted seedlings, mainly in terms of efficiency in the absorption and translocation of nutrients to the scion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies on pre-fruiting mango trees primarily focus on the vegetative growth of plants (Whiley et al 1989, Luvaha et al 2008, Mng'omba et al 2010, Pinto et al 2018. A few studies of gas exchange at this stage have been conducted under controlled conditions (Allen et al 2000, Allen and Ort 2001, Luvaha et al 2007).…”
Section: Introductionmentioning
confidence: 99%